The Effect Addition of Winged Bean and Konjac Flour on the Quality of Instant Cassava-Corn Noodles - Satrijo Saloko; Siska Cicillia; Siti Rakmah (Future Science)
This study aims to determine the effect of addition winged bean and konjac flour on the quality of instant corn noodles. The experimental design used was a Completely Randomized Design (CRD) with one factor. The factor which is done in the formulation of adding winged bean flour and konjac flour consisting of six treatments. The treatment was P (presentation of cornflour : mocaf: konjac flour : winged bean flour) included P1 (65% : 20% : 0% : 15%); P2 (65% : 20% : 3% : 12%); P3 (65% : 20% : 6% : 9%); P4 (65% : 20% :9% : 6%); P5 (65% : 20% : 12% : 3%) and P6 (65% : 20% : 15% : 0%). The measured parameters of noodle quality are water content, protein content, dietary fiber content, fat content, calcium content, color, cooking time, cooking loss, rehydration, and organoleptic quality including taste, aroma, and texture. The addition of winged bean flour and konjac flour gives a significantly different effect on Moisture content, protein content, dietary fiber content, fat content, Ca content, Zn content, color, cooking loss, cooking time, rehydration, hedonic aroma, and taste both hedonic and scoring. The best treatment was obtained in the treatment of P3 (9% winged bean flour: 6% konjac flour) with a water content of 4.50%; protein content 11.39%; dietary fiber content of 20.01%; fat content 2.74%; Calcium content 0.06%; Zink content 2,84 ppm; L value of 59.59 before brewing and 50.15% after brewing; °hue before brewing 76.11 and after brewing 77.93; cooking time 10.32 minutes; cooking loss 0.66% and rehydration 10.18 minutes.